Beyond tranquility: Buddhist meditations in essay and verse - Genoud, Charles (Wisdom Publications, 2020)
"Essays, meditations, and poetry on Buddhism. From the introduction: The meditations described in this book are based on the Theravada Buddhist tradition, mainly as taught in Burma, and on the Tibetan tradition, with a few remarks taken from Zen. These approaches complement each other. Vipassana, a characteristic Theravada practice following the Satipatthana Sutta, is very careful to include in meditation all aspects of life, such as the body, feelings, thoughts, emotions, and mental states, negative as well as positive. The Tibetan tradition analyzes thoughts and emotions in great depth, to discover the elusive nature of consciousness and of the world. Zen approaches meditation in a comprehensive manner as it integrates simple movements and daily activities. Because empathy must supplement wisdom in order to ensure responsible behavior in the world, a meditation on kindness also appears in this book. The texts most frequently cited to describe meditation are early Sutras: the Satipatthana Sutta, the Bahia Sutta, the Malunkyaputta Sutta, the Sivaka Sutta, and the Kaccayanagotta Sutta. For the meditations on thoughts and emotions, passages from early Tibetan texts are used, as well as the oral teachings of the great twentieth-century Tibetan master Dilgo Khyentse Rinpoche. In general, the philosophical point of view expressed here is consistent with the texts of the great Indian Buddhist philosopher Nagarjuna as well as with the Vimalakirti Sutra, one of the main sutras that expounds the "middle way", the Madhyamaka philosophy. Teachers from other spiritual traditions are also cited here, including Saint Augustine, Meister Eckhart, and Martin Buber. They shed light on certain important aspects of the spiritual path and are a great source of inspiration. Any system of thought is eventually caught in its own game. The study of other systems may help to avoid that fate, at least partially. The reification of the Buddha nature by certain authors-the erroneous interpretation of it as a kind of "thing" to be grasped-can serve as an example. Meister Eckhart specifically underlines the danger of grasping at the ultimate when he teaches that we must pray to God to free us of God. The reflections presented in the second part of this book draw on even more varied sources. The chapter in that section on the investigation of consciousness was enhanced by the readings of Jean-Paul Sartre's early texts, such as The Imagination, the Imaginary, Emotions: Outline of a Theory ...